2015
DOI: 10.1590/0001-3765201520140315
|View full text |Cite
|
Sign up to set email alerts
|

Growth curve by Gompertz nonlinear regression model in female and males in tambaqui (Colossoma macropomum)

Abstract: Was evaluated the pattern of growth among females and males of tambaqui by Gompertz nonlinear regression model. Five traits of economic importance were measured on 145 animals during the three years, totaling 981 morphometric data analyzed. Different curves were adjusted between males and females for body weight, height and head length and only one curve was adjusted to the width and body length. The asymptotic weight (a) and relative growth rate to maturity (k) were different between sexes in animals with ± 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 13 publications
3
25
1
1
Order By: Relevance
“…Breeding program families registered gains over 29.0% when compared to those in current assay, and in less time, emphasizing the importance of breeding program for tambaqui. Mello et al (2015) reported higher growth rates than those given by these authors and rates close to those in current assay, featuring growth rates at 8.66 g/day and 9.34 g/day, respectively for male and female tambaquis. …”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Breeding program families registered gains over 29.0% when compared to those in current assay, and in less time, emphasizing the importance of breeding program for tambaqui. Mello et al (2015) reported higher growth rates than those given by these authors and rates close to those in current assay, featuring growth rates at 8.66 g/day and 9.34 g/day, respectively for male and female tambaquis. …”
Section: Resultssupporting
confidence: 74%
“…This feature is undesirable since it provides smaller carcass yield (REIDEL et al, 2004;BOMBARDELLI et al, 2005;ADAMES et al, 2014). In fact, Mello et al (2015) observed that there were differences in the growth pattern of the size of the head in tambaquis, or rather, females had a higher growth rate (albeit slow) when compared to males. However, the authors continued their assay till the sexual maturity of the tambaquis (three years), whereas fish in current assay were assessed in less than half that time (481 days) and without sexual differentiation, which impairs any comparison.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, on the premise that females mature later than males, the nutrients from diet would be directed to muscle growth and weight gain, leading females to reach a larger size. However, this is not valid for the tambaqui once the commercial slaughter takes place before the fish reach sexual maturity (Mello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%